Growth hacking adoption in focus : Developing scale and enhancing the nomological network of its antecedents - Bani-Melhem, Shaker; Akhtar, Muhammad Waheed; Zahoor, Nadia; Khalid, Adeel; Usman, Muhammad (Elsevier, 2025)
Given the importance of growth hacking for the long-term success of businesses and the lack of empirical research, we draw on dynamic capability theory to propose a model that explicates how and when entrepreneurial leadership leads to growth hacking adoption in the startup context. Two studies were conducted to test the proposed model. Specifically, in Study 1, we developed a 15-item scale (five dimensions) of growth hacking adoption based on 207 responses from the owners of various startups in Morocco. Study 2 was based on time-lagged data from 305 owners of startups in China. Our results reveal that entrepreneurial leadership positively impacts growth hacking adoption directly and via big data capability and organizational learning ambidexterity. Further, leader conscientiousness moderates the effects of entrepreneurial leadership on big data capability. We provide actionable insights for owners/managers of start-ups to foster learning ambidexterity and drive growth hacking.
Keywords: Growth hacking; Entrepreneurial leadership; Big data capability; Learning ambidexterity; Leader conscientiousness; Start-up businesses; startup companies